Common Economic Space between EU and Russia? - L. Voronkov (Vestnik MGIMO-Universiteta)
The possibilities and prospects of building a Common Economic Space (CES) between Russia and the EU in accordance to the "Road map", signed by the parties in 2005, are analyzed in this article. It outlines the economic essence of the different measures being undertaken within the EU and the benefits for countries and companies with high level of competitiveness on the EU markets, being gained from participation in the EU integration processes. The main elements of the European Economic Area (EEA), which has been created by the agreement between EU and EFTA in 1993, are examined as well as the rights and obligations of the parties involved. The author considers the peculiarities and consequences of participation of Central and Eastern European countries in the EU that prompted the European Union to initiate the "neighborhood policy" and Eastern partnership project for the Eastern Europe countries, which are not members of the EU. The author analyses the main purposes of the "neighbourhood policy", as they are outlined by the EU Directorate General for external affairs, as well as the possible consequences of their implementation for the states, included by the EU in its "circle of friends". On this background the possibilities and perspectives for the creation ofaCES between the EU and Russia with particular regard to the peculiarities of integration processes within the post-Soviet space are considered. The author concludes that the creation of a CES between the EU and Russia is hardly feasible on the grounds, envisaged by the EU.